Integration of Learning Outcome Taxonomy with the Objectives of Islamic Religious Education in the Era of Society 5.0 (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2026)
This article aims to conceptually analyze the integration of the learning outcomes framework with the orientation of Islamic Religious Education in responding to the dynamics of a digital society oriented toward human-centered development. Technological advancement requires religious education to emphasize not only knowledge mastery but also the formation of moral attitudes, spiritual values, and practical competencies of students. This study employs a qualitative approach through library research by analyzing academic books, national and international journal articles, and relevant educational policy documents. Data were analyzed using content analysis to examine the relationship between cognitive, affective, and psychomotor dimensions within a holistic Islamic education framework. The findings indicate that the integration of learning outcomes taxonomy (cognitive, affective, psychomotor) strengthens Islamic Religious Education learning systematically and holistically. The cognitive domain builds understanding of Islamic teachings, the affective domain internalizes spiritual-moral values, and the psychomotor domain actualizes practice in real life. In the context of Society 5.0, Islamic Religious Education plays a strategic role in fostering digital literacy based on Islamic values, technology ethics, and humanistic awareness. This integration has implications for formulating holistic objectives, participatory teaching strategies, and comprehensive, authentic assessment, enabling Islamic Religious Education to develop a generation that is faithful, morally noble, and wise in utilizing technology.